The Experience of Solidarity in Poland under Communist Rule and Thereafter - Magdalena Solska (sozialpolitik.ch, 2021)
Although Solidarność was the largest mass movement in the history of after-war Europe, the experience of solidarity during that time in communist Poland has barely been analysed. Drawing on historical accounts of the events in the 1980s and press interviews with Solidarność members, this paper attempts to bridge this gap and identifies key aspects of the experienced solidarity. It argues that the solidarity under communism in Poland derived not only from the common enemy – the communist party state – but was deeply rooted in Catholic social thought and the national identity. It was driven mainly by ideas of protection of human dignity, mutual aid, participation and a demand for “life in truth”. Since 2015, the new social policy has had initially positive impact on income inequality, birth rates and poverty but must be accompanied by further measures to obtain a long-term character.